Development of Canva-Assisted Interactive Learning Media Based on Guided Discovery Learning on Chemical Reactions for Phase E Senior High School Students - Nofri Yuhelman; Ezi Fitri Yani (Jurnal Riset Pendidikan Kimia (JRPK), 2026)
This study aimed to develop Canva-assisted interactive learning media based on the Guided Discovery Learning model for teaching chemical reactions to Phase E senior high school students. The increasing integration of digital technology in education requires instructional media that promote active learning and enhance students’ conceptual understanding. This study employed a Research and Development (R&D) method using the 4-D model, consisting of the define, design, develop, and disseminate stages, although the research was limited to the develop stage. The novelty of this study lies in integrating Canva-assisted interactive learning media with Guided Discovery Learning in Phase E chemistry learning under the Merdeka Curriculum. The developed media was validated by five experts, while practicality was evaluated by two teachers and 32 Phase E students using validation sheets and practicality questionnaires. Validity was analyzed using Aiken’s V, and practicality was determined through percentage analysis. The results showed an average Aiken’s V value of 0.92, indicating high validity, while practicality scores reached 96% from teachers and 93% from students. These findings provide empirical evidence that the developed media is valid, highly practical, and suitable as an alternative instructional resource for chemistry learning. This media is therefore recommended for use by teachers as an innovative and engaging tool to support the implementation of student-centered chemistry instruction in senior high schools.